The Utility of Tacit Knowledge in Corporate Renewal - Ney, Piotr (Użyteczność wiedzy ukrytej w procesie transformacji przedsiębiorstwa, 2010)
Corporate renewal programs usually address tangible elements such as the organizational structure, processes and infrastructure, as well as the explicit knowledge of workers through training or coaching. Such programs do not usually address the tacit knowledge of workers. Tacit knowledge, the personal and specialized professional knowledge that individual workers develop to succeed in performing complex roles, is often a significant corporate resource. It can have a positive utility in helping workers adapt quickly to the renewed organization. However, it can also act as a strong constraint to change. This article discusses tacit knowledge within the context of organizational renewal programs, and suggests some practical techniques for positively influencing its utility.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 55-68
Keywords: tacit knowledge; organisational transformation; metaphors; storytelling